2015
DOI: 10.1186/s12943-015-0439-5
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoproteomic analysis reveals Smarcb1 dependent EGFR signaling in Malignant Rhabdoid tumor cells

Abstract: BackgroundThe SWI/SNF ATP dependent chromatin remodeling complex is a multi-subunit complex, conserved in eukaryotic evolution that facilitates nucleosomal re-positioning relative to the DNA sequence. In recent years the SWI/SNF complex has emerged to play a role in cancer development as various sub-units of the complex are found to be mutated in a variety of tumors. One core-subunit of the complex, which has been well established as a tumor suppressor gene is SMARCB1 (SNF5/INI1/BAF47). Mutation and inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Similarly, Kuwahara et al found that RT cell lines displayed high levels of EGFR expression and inhibiting EGFR phosphorylation with the EGFR TKI gefitinib was capable of reducing cell growth both in vitro and in vivo [7]. These findings are consistent with a recent phosphoproteomic analysis of Smarcb1-deficient RT murine cells derived from a genetically engineered mouse model which showed that Smarcb1 loss led to the upregulation of EGFR phosphorylation and activation of the AKT pro-survival pathway [6]. Interestingly, in this study, lapatinib suppressed EGFR phosphorylation while gefitinib had the opposite effect of elevating receptor activation, although the mechanistic basis of this counterintuitive finding was not pursued.…”
Section: Editorialsupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, Kuwahara et al found that RT cell lines displayed high levels of EGFR expression and inhibiting EGFR phosphorylation with the EGFR TKI gefitinib was capable of reducing cell growth both in vitro and in vivo [7]. These findings are consistent with a recent phosphoproteomic analysis of Smarcb1-deficient RT murine cells derived from a genetically engineered mouse model which showed that Smarcb1 loss led to the upregulation of EGFR phosphorylation and activation of the AKT pro-survival pathway [6]. Interestingly, in this study, lapatinib suppressed EGFR phosphorylation while gefitinib had the opposite effect of elevating receptor activation, although the mechanistic basis of this counterintuitive finding was not pursued.…”
Section: Editorialsupporting
confidence: 68%
“…Loss of SMARCB1 is a driver in a number of cancer types, including rhabdoid tumors (RTs), epithelioid sarcomas, renal medullary carcinoma, epithelioid malignant peripheral nerve sheath tumors, meningiomas and extraskeletal myxoid chondrosarcomas [5]. Tyrosine kinase dependencies associated with SMARCB1 deficiency have been most well studied in RTs and include oncogene addiction to the epidermal growth factor receptor (EGFR) and Human EGFR 2 (HER2) [6][7][8]. Screening three RT cell lines across a panel of 129 small molecular inhibitors, Singh et al showed that targeting EGFR-HER2 signaling using the EGFR-HER2 TKI lapatinib was effective in blocking tumor cell migration and inducing apoptosis in vitro [8].…”
Section: Editorialmentioning
confidence: 99%
“…Wöhrle et al. (2013) showed that FGFR1 is upregulated when SMARCB1 is deleted in MRT cells, while Darr et al. (2015) recently demonstrated that EGFR expression is regulated by SMARCB1.…”
Section: Discussionmentioning
confidence: 99%
“…As to Egfr , a considerable number of publications have indicated the consistency between the RNA expression level and protein level [4951]. However, a relatively large number of genes including its ligands are in the pathways in regulation of Egfr .…”
Section: Discussionmentioning
confidence: 99%